Isolation and antidiabetic Activity of Prenylated Xanthones from Pericarp of Mangosteen (Garacinia Mangostana Linn.) - Karneg, Syahdam; Fadlan, Arif; Ersam, Taslim (IPTEK Journal of Proceedings Series, 2020)
The material used in this research was dry powder of pericarp mangosteen (Garcinia mangostana Linn.). which is a family plant of Clusiaceae. This taxa is known as the main source of prenylated xanthones derived from phenolic compounds. The compounds separation process was carried out by maceration method, 8 kg of sample macerated using n-hexane solvent, 90 g of n-hexane extract were produced. The n-hexane extract was fractionated by vacuum liquid chromatography (VLC) using silica gel, eluted by increasing the polarity of the solvent, which is a mixture of n-hexane solvent: dichloromethane (10%, 20%, 30% and 50%), resulting in three combined fractions, namely the first fraction 13,92 g, the second fraction 18,27 g, and the third fraction 23,24 g. The refraction process was then carried out in the third fraction, producing two yellow crystals with melting points respectively, 155-156 Â°C and 172-173 Â°C. The structural elucidation method was carried out using UV-Vis, IR, HR-ESI-MS, and NMR spectroscopy techniques. Based on the analysis of spectrum data from two known compounds, 8-deoxygartanin (1) and Î²-mangostin (2) antidiabetic bioactivity test was carried out by the method of inhibiting the enzyme Î±-glucosidase in vitro. The test results obtained by compound (1) with an IC50 value of 38,5 Î¼M and compound (2) with an IC50 value of 157,9 Î¼M indicate that the two compounds are included in the inactive category. This is indicated by the IC50 value which is much higher when compared to the acarbose as a positive control with an IC50 value of 4.5 Î¼M.